Audit Tests and Their Impact on Fraud Detection-Case of Albania - MITI, Mirela Ujkani; Myftaraj (Tomori), Elena; Hajrullaj, Ueda (European Journal of Economics and Business Studies, 2018)
For an auditor having the responsibility for the prevention, detection and reporting of fraud, other illegal acts and errors is one of the most controversial issues in auditing, and has been one of the most frequently debated areas amongst auditors, politicians, media, regulators and the public (Gay et al 1997). The primary objective of financial reporting is to provide high-quality information to financial statement users. Regarding to this, we have taken into consideration an important element, such as the audit report which provides reasonable assurance to present and potential capital providers and other stakeholders when making investments, credit decisions, and allocating resources that may enhance overall capital market efficiency. The audit engagement in Albania is based on International Auditing Standards. We have attempted to study and identify the role of audit tests, performed by auditors during the audit process, in detecting material misstatements in the financial statements, in order to obtain a more qualitative financial reporting. Through the literature study regarding the impact of audit procedures undertaken in the auditor's opinion and the evidence gathered by the questionnaire addressed to auditors in Albania, it is possible to carry out our research questions about the subject field. In conclusion, we will express our opinion about the possible suggestions that should be followed during the selection of the adequate audit test to be performed, in order to ensure the most qualitative financial reporting in Albania.
Keywords: financial reporting, audit, accounting, audit tests.